The euro area bank lending survey: Role, development and usein monetary policy preparation - Petra Köhler-Ulbrich; Hannah S. Hempell; Silvia Scopel (European Central Bank (ECB), 2016)
The euro area bank lending survey (BLS) serves as an important tool in the analysis of bank lending conditions in the euro area and across euro area countries, providing otherwise unobservable qualitative information on bank loan demand and supply from/to euro area enterprises and households. Since its introduction in 2003, the BLS has received growing attention and has become of key importance for the analysis and assessment of bank lending conditions in the euro area and at the national level. In particular in the context of the financial crisis, the BLS was used to gather additional information on the impact of the crisis and of the ECB's monetary policy measures on banks' funding situation and bank lending conditions. Following a description of the design and development of the BLS, this paper focuses on the analysis of bank lending supply and demand in the euro area and on their contributing factors. The results of the BLS are put into a wider economic perspective by relating them to other macroeconomic and financial variables. Analyses based on individual bank replies complement the picture further by providing more granular evidence on loan developments. In addition, an overview of the use of the euro area BLS as an analytical tool for investigating bank lending conditions in the euro area is presented.
Keywords: E44; E5; G21; 330; bank lending conditions; euro area; loan demand; loan supply; monetary policy; monetary policy transmission